Akad take over berdasarkan konsep kemaslahatan dalam perbankan syariah - Noegroho, Any; Noor, Syamhudian; murhaini, Suriansyah (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
This study addresses the challenges faced by customers in the debt transfer (take over) process in Islamic banking, particularly the need for a practical application of the concept of maslahah (welfare) in aligning financial transactions with Sharia principles. Islamic banking, as a trusted institution, provides ethical financing solutions based on justice and welfare, and the debt transfer product serves as a means for customers to move their debts from conventional banks to Islamic banks, ensuring adherence to Sharia values. The objective of this study is to identify the specific mechanisms of the debt transfer contract, evaluate its impact on customer welfare, and examine the practical implementation of the maslahah concept in this product. This research employs a qualitative approach, including interviews with bank representatives and analysis of relevant Sharia banking documents, to gain insights into the process and outcomes of debt transfer contracts. The study finds that the debt transfer contract not only serves as a financial tool but also reflects Islamic banks' commitment to customer welfare by providing an alternative free from interest-based practices. This research contributes to the literature by introducing innovative approaches in debt transfer contracts and reinforcing the role of maslahah in Islamic banking, offering practical solutions for promoting economic welfare and justice. The study also focuses on Bank Syariah Indonesia as a case study, contributing to the broader understanding of the development of Islamic banking in Indonesia. The findings highlight the importance of applying maslahah as a principle of economic welfare and justice within Islamic finance.